Electrophysical properties of metal-semiconductor-metal structures based on isovalently doped zinc selenide crystals - Chugai, O.; Ryzhikov, V.; Starzhinskiy, N.; Oleynik, S.; Katrunov, K.; Zenya, I. (Functional Materials, 2004)
Electric capacitance C and dielectric losses tgδ have been determined for metal-semiconductor-metal structures based on isovalently doped ZnSe crystals. It has been shown that annealing of the grown crystals in zinc atmosphere causes the increase of C by 2-3 orders of magnitude. This parameter, as well as tgδ becomes dependent upon the bias voltage U, with regions of negative and of positive slope observed on the C(U) plots. It has been shown that dependences C(U) and tgδ(U) are determined by changes with voltage in the two oppositely switched Schottky barriers.